The New Zealand Biodiversity Factor—Residential (NZBF-R): A Tool to Rapidly Score the Relative Biodiversity Value of Urban Residential Developments - Theis, Jacqueline; Woolley, Christopher K; Seddon, Philip J; Shanahan, Danielle F; Freeman, Claire; Pedersen Zari, Maibritt; van Heezik, Yolanda (MDPI AG, 2025)
The loss of biodiversity in urban residential areas that are densifying in response to increasing housing demand has serious implications for urban ecosystem functioning and human wellbeing. There is an urgent need for integrating biodiversity-sensitive design into urban planning and development. While several existing “Green Factor” tools guide greening strategies in cities, none have biodiversity as their primary focus. We describe here a tool that specifically evaluates biodiversity in residential developments, with a particular emphasis on supporting native biodiversity. The NZBF-R (New Zealand Biodiversity Factor—Residential) also educates users through embedded explanations on how various design features positively impact biodiversity and it provides tailored recommendations for effective biodiversity enhancement, enabling urban professionals to make informed landscape design decisions. Developed through literature review, analyses of existing Green Factor tools, and a robust weighting process, the NZBF-R identifies and ranks characteristics that support urban biodiversity, based on evidence from the scientific literature. We demonstrate the application of the NZBF-R on one case study. The NZBF-R can be applied across the planning, design, and retrofitting stages of urban residential projects, making it a valuable resource for urban planners and designers.
Keywords: 33 Built Environment and Design; 3301 Architecture; 3304 Urban and Regional Planning; Generic health relevance; 0502 Environmental Science and Management; 3301 Architecture; 3304 Urban and regional planning; 4104 Environmental management